Within-Person Variability in Job Performance - Dalal, Reeshad S.; Bhave, Devasheesh P.; Fiset, John (Journal of Management, 2014)
Although both researchers and practitioners know that an employee’s performance varies over time within a job, this within-person performance variability is not well understood and in fact is often treated as error. In the current paper, we first identify the importance of a within-person approach to job performance and then review several extant theories of within-person performance variability that, despite vastly different foci, converge on the contention that job performance is dynamic rather than static. We compare and contrast the theories along several common metrics and thereby facilitate a discussion of commonalities, differences, and theory elaboration. In so doing, we identify important future research questions on within-person performance variability and methodological challenges in addressing these research questions. Finally, we highlight how the conventional practical implications articulated on the basis of a static, between-person perspective on job performance may need to be modified to account for the dynamic, within-person nature of performance.